2006
DOI: 10.1016/j.jcrs.2006.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, repeatability, and reproducibility of Artemis very high-frequency digital ultrasound arc-scan lateral dimension measurements

Abstract: Purpose-To determine the accuracy, repeatability, and reproducibility of measurement of lateral dimensions using the Artemis (Ultralink LLC) very high-frequency (VHF) digital ultrasound (US) arc scanner. Setting-London Vision Clinic, London, United Kingdom.Methods-A test object was measured first with a micrometer and then with the Artemis arc scanner. Five sets of 10 consecutive B-scans of the test object were performed with the scanner. The test object was removed from the system between each scan set. One e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
1
21
1
Order By: Relevance
“…The within-eye standard deviation for both angle diameter (0.13 mm) and sulcus diameter (0.23 mm) was higher than that which we reported when measuring an inanimate test object (0.04 mm) using the same scanner that was used for the present study 25. Although every effort was made to obtain scans in the same horizontal meridian, this variability is likely due to slight variation in the scan plane between scans and measurement error caused by observer judgment of the fiducial points.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The within-eye standard deviation for both angle diameter (0.13 mm) and sulcus diameter (0.23 mm) was higher than that which we reported when measuring an inanimate test object (0.04 mm) using the same scanner that was used for the present study 25. Although every effort was made to obtain scans in the same horizontal meridian, this variability is likely due to slight variation in the scan plane between scans and measurement error caused by observer judgment of the fiducial points.…”
Section: Discussioncontrasting
confidence: 75%
“…The Artemis 1 VHF digital ultrasound arc-scanner has previously been shown to obtain measurements on a test object with lateral dimensions of the size commonly found in the anterior segment with accuracy of 0.00 mm, repeatability of 0.04 mm, and reproducibility of 0.01 mm 25. We set out to investigate the accuracy of estimating angle diameter and sulcus diameter from external measurements by analyzing the direct correlations between white-to-white, angle diameter, and sulcus diameter as well as multivariate correlations including other conventional external measurements—manifest refraction, ACD, corneal curvature, central corneal thickness (CCT), and age.…”
mentioning
confidence: 99%
“…Indeed, Characteristics such as accuracy, repeatability, reproducibility, and axial and lateral resolution of both technologies have been reported in previous studies. [14][15][16][17][18][19][20][21][22][23][24][25][26] We used the same basic study protocol in the autopsy eyes and clinical studies reported here and found that the internal dimensions of the anterior segment of the human eye varied significantly between the 4 meridians considered, regardless of the technology, observer, or eye series.…”
Section: Discussionmentioning
confidence: 99%
“…Very high frequency ultrasonography (VHF US), [14][15][16][17][18] and anterior segment optical coherence tomography (AS-OCT) [19][20][21][22][23][24][25][26] represent promising technologies for noninvasive imaging of the anterior segment of the eye. The aim of this study was to determine whether internal dimensions of the anterior segment of the human eye, such as angle-to-angle (A-A) and sulcus-to-sulcus (S-S) dimensions, are significantly different along 4 different meridians.…”
mentioning
confidence: 99%
“…The Artemis 1 has been used to measure flap thickness reproducibility 22,23 ; provide diagnoses for optical complications after corneal refractive surgery 24-26 ; demonstrate epithelial changes after myopic LASIK, 27 hyperopic LASIK, 28 and orthokeratology 29 ; investigate the sizing issues related to phakic intraocular lenses (IOLs) 30-33 ; measurement of stromal change to evaluate excimer laser ablation depth 34 ; describe the epithelial thickness 35 and stromal thickness 36 in a normal population; describe corneal, epithelial, and stromal thickness in a keratoconic population 37 ; and using epithelial thickness profiles to screen for keratoconus. 38,39 The Artemis 1 prototype was used for the present study.…”
mentioning
confidence: 99%